Application of Six Sigma metrics for assessing the quality management of biochemical analytes in the clinical laboratory - Saurabh Singh; Manisha Singh; Devesh Sharma; Ijen Bhattacharya; Mamta Padhy; Surabhi Puri; Utkarsh Singh Tomar (Asian Journal of Medical Sciences)
Background: Quality control (QC) is an important part of clinical laboratory management which evaluates and maintains the performance of the clinical laboratory. Six Sigma is a continuous quality improvement process which is widely applied in the health care industry mainly in clinical laboratories.